2022
DOI: 10.3847/1538-4357/ac7c6d
|View full text |Cite
|
Sign up to set email alerts
|

Young, Blue, and Isolated Stellar Systems in the Virgo Cluster. I. 2D Optical Spectroscopy

Abstract: We use panoramic optical spectroscopy obtained with the Very Large Telescope/MUSE to investigate the nature of five candidate extremely isolated low-mass star-forming regions (Blue Candidates; hereafter, BCs) toward the Virgo cluster of galaxies. Four of the five (BC1, BC3, BC4, and BC5) are found to host several H ii regions and to have radial velocities fully compatible with being part of the Virgo cluster. All the confirmed candidates have mean metallicity significantly in excess of that expected from their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Sand et al (2015) searched for other objects with similar optical and UV morphology to SECCO 1, identifying five additional candidates in Virgo. With Hubble Space Telescope (HST) imaging, plus Jansky Very Large Array (VLA), GBT, and Multi Unit Spectroscopic Explorer observations (Jones et al 2022a(Jones et al , 2022bBellazzini et al 2022), we demonstrated that four 11 of these are analogous to SECCO 1 (though not all are H I-rich) and argued that they represent a new class of object, which we will refer to simply as "blue blobs." The only viable mechanism to explain both the isolation and young ages of blue blobs is high-speed ram pressure stripping of H Ibearing galaxies falling into the cluster (Jones et al 2022b).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sand et al (2015) searched for other objects with similar optical and UV morphology to SECCO 1, identifying five additional candidates in Virgo. With Hubble Space Telescope (HST) imaging, plus Jansky Very Large Array (VLA), GBT, and Multi Unit Spectroscopic Explorer observations (Jones et al 2022a(Jones et al , 2022bBellazzini et al 2022), we demonstrated that four 11 of these are analogous to SECCO 1 (though not all are H I-rich) and argued that they represent a new class of object, which we will refer to simply as "blue blobs." The only viable mechanism to explain both the isolation and young ages of blue blobs is high-speed ram pressure stripping of H Ibearing galaxies falling into the cluster (Jones et al 2022b).…”
Section: Introductionmentioning
confidence: 97%
“…Beccari et al (2017) andBellazzini et al (2022) measured the metallicities of five blue blobs (SECCO 1, BC1, and BC3-5) using the same line ratio metrics as used here (see Section 3.5) and found a range of <…”
mentioning
confidence: 99%